2018
DOI: 10.1021/acsenergylett.7b01257
|View full text |Cite
|
Sign up to set email alerts
|

Crown Ethers Enable Room-Temperature Synthesis of CsPbBr3 Quantum Dots for Light-Emitting Diodes

Abstract: The synthesis of all-inorganic cesium lead halide perovskite quantum dots (QDs) typically requires high temperatures, stringent conditions, large quantities of surface ligands, and judicious purification steps to overcome ligand-induced charge injection barriers in optoelectronic devices. Low-temperature syntheses generally require lower ligand concentrations, but are severely limited by the low solubility of the Cs precursor. We describe an innovative and general approach under ambient conditions to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 35 publications
2
69
0
1
Order By: Relevance
“…A post-synthesis treatment with PbBr2 (185 mg/ml) dissolved in 1:1:1 Propionic Acid:Butylamine:Hexane in volume was carried out to enhance the PLQY (see ref. 25,12 l for a typical synthesis). After the treatment, oleic acid (35 l for a typical synthesis) was added to the solution to dissolve the NC aggregates observed under TEM.…”
Section: Methodsmentioning
confidence: 99%
“…A post-synthesis treatment with PbBr2 (185 mg/ml) dissolved in 1:1:1 Propionic Acid:Butylamine:Hexane in volume was carried out to enhance the PLQY (see ref. 25,12 l for a typical synthesis). After the treatment, oleic acid (35 l for a typical synthesis) was added to the solution to dissolve the NC aggregates observed under TEM.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was shown by Fang et al that polar solvent controlled ionization method was used to obtain CsPbX 3 NCs with high PLQYs, narrow FWHM, large Stokes shifts, and particular morphology. [36]…”
Section: Room-temperature Methodsmentioning
confidence: 99%
“…Besides, they also found the CsPbBr 3 NCs have better stability (Figure d). Veldhuis et al . used crown ethers to increase solubility of Cs precursors in polar media where they obtained bright green emission LEDs (Figure e).…”
Section: Synthesis Of Cspbx3‐ncsmentioning
confidence: 99%
“…These ligands can saturate the dangling bonds on the NC surface, increase solubility, and control the nucleation and growth kinetics of NCs, as well as screen the NCs to avoid sedimentation. For example, Veldhuis et al found that crown ethers can increase the solubility of the Cs 2 CO 3 precursor, which allowed for low‐temperature synthesis …”
Section: Introductionmentioning
confidence: 99%